Putting The Herbal Medicine into The Modern Anti-Hypertension Armamentarium: Hibiscus Sabdariffafor Hypertension? - Anwar Santoso (Jurnal Kardiologi Indonesia, 2012)
Herbal medicine has been moving from fringe to mainstream use with a substantial number of patients seeking remedies, which free from side effects caused by synthetic chemicalÂ  medicines. Recently, professional societies try to utilize eco-friendly and bio-friendly plant-based products for the prevention and cure of degenerative disease, such as: hypertension, diabetes and cancer. It has been known that synthetic chemical medicines used in the above generative disease is not free from adverse effects, let alone the usage of those medicinesÂ  should be long standing.